Artistic child labor: the legal protection of homeland labor (Research, Society and Development, 2022)
The present work has the fundamental purpose of analyzing the development of children's artistic work in the face of the prohibition of child labor in the country's legal system. Therefore, a synthesis about child labor in Brazil is presented, followed by an approach that proposes to critically discuss the harmonic social acceptance of this activity, since these artistic representations, carried out in the most diverse scenarios, are socially accepted indiscriminately. Focusing on the limits imposed by labor legal protection, the rule and the exception are addressed. Integral protection based on the constitutional principle of human dignity, permission and prohibition – from freedom of expression to relevant rights – and whether the work is developed in an adequate manner to the conditions and legal protection of the child is analyzed. The methodology used is deductive, establishing an approach based on doctrinal, legislative and jurisprudential review on the subject, and with an explanatory and informative purpose, which seeks to clarify the main aspects of artistic child labor in Brazil.